Occupational therapy and assistive technology - Rodrigues, Heli de Oliveira; Buin, Luciana; Pereira, Ana Julia Arnoni Thomaz; Landim, Síbila Floriano (Seven Editora, 2023)
According to the World Health Organization (WHO), the state of health of an individual is not due to the absence of disease, but to a complete state of physical, mental and social well-being. The new concepts pointed out by the International Classification of Disability and Health Functionality (ICF), appropriates a new view on the concept of disability, transferring this scope that the architectural barriers, social conducts and technological resources are situations amenable to the inclusion of the individual in the social sphere.Based on this assumption, we can interpret that the individual should be seen and cared for holistically. We should promote social spaces where diversity is favored, creating possibilities for inclusion of people with disabilities or reduced mobility through assistive technology resources (Pelosi, 2007).DOI:https://doi.org/10.56238/alookdevelopv1-169